ANALISA PERANCANGAN ALAT SIMULATOR GELOMBANG QRS SEBAGAI PENGENALAN POLA GELOMBANG ELEKTROKARDIOGRAF - Evrita Lusiana Utari (Teknoin, 2016)
Simulator machine of QRS wave has the input of PQRST as well as electrocardiograph wave parameter. The input of PQRST wave is tuned by setting the value of its amplitude and wavelength. The value is chosen based on the heart patients data that have been previously recorded. The validation value corresponds to the regulator value. Further, the validation value is compared to the short term electrocardiograph data that have been recorded for 5 minutes. The statistical and histogram based time domain analysis method are the two simplest analysis method of heart rate variation. The statistical analysis consists of two steps, i.e. the average and standard deviation of normal heart rate direct measurement. This measurement yields a negative deflection value of Q from R wave of 25%, a positive deflective value of R wave of 1.6-3 mV, and a negative deflection of S wave of 0.1-.5 mV.